Advancements in Soft Robotic Implants for Long-Term Drug Delivery and Tissue Monitoring - Yadav, Ajay; Rai, Vishal; Singh, Shekhar; Kanojia, Akanksha (Journal for Research in Applied Sciences and Biotechnology, 2024)
Soft robotic implants are a major upgrade in medical devices providing novel means for long-term drug administration and tissue tracking. The eco-friendly biodegradable body-prosthetic will not only be compatible with the human body, but can also mingle completely without inducing foreign-body responses and discomfort. Since these implants provide programmed and localized drug delivery; hence the significance of these sutures could be found in administering the drugs at a specific site and specific interval so as to diminish the side effects and improved therapeutic outcomes. Modern developments of soft robotics implants have improved their design, performance, interaction with biological and other natural materials. Material developments are becoming smarter, where responsive materials in the form of: smart materials, which can react to environmental stimuli and adjust drug delivery rates immediately (and); etc. Moreover, the evolution of microfabrication and nanotechnology also created high precision and less invasive devices, rendering more efficient and well-accepted to patients. These implants are especially valuable for long-term afflictions like diabetes and cancer as they streamline the ongoing, precise delivery of medications. They also have a crucial role in pain management and postoperative care, effectively providing prolonged release of analgesics, and ultimately enhance patient comfort thus contributing to smoother recovery. For tissue monitoring, implantable flexible soft robotic devices with integrated sensors and actuators are able to provide real-time data collection and analysis for the continuous monitoring of vital physiological information, such as cardiovascular health, neural activity, skin conditions (wound healing) etc. This is important, particularly for early detection of complications and receiving timely interventions to optimize patient outcomes. In the future there are a number of intriguing applications that could be developed with these soft robotic implants like personalized medicine and integration with other state-of-the-art medical technologies. Further research and development should/hopefully will address outstanding challenges e.g. technical, regulatory etc to allow more wide-ranging clinical application with consequent transformative impacts on healthcare. Finally, soft robotic implants show great potential to improve drug delivery and tissue monitoring, with continuous development bringing the field closer to better performing medical solutions.